ANALISIS RESTATEMENT DALAM PENERAPAN AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL Pada Badan Pemberdayaan Masyarakat dan Pemerintahan Desa (BPMPD) Daerah Provinsi Sulawesi Tengah - Marjuni, Marjuni (Katalogis, 2017)
One of the implementation of government regulation No. 71 of 2010 on the accounting system of government and regulatory of Home Affairs Minister No. 64 of 2013 on the application of the accrual-based of local government accounting system is restatement; balance sheet that needs to be restated at the beginning of the periode when the local government will implement the new accounting policy from cash toward accrual to a full accrual basis. Restatetments needed for balance sheet whose policies have not followed the full accrual basis. For the preparation of balance sheet on accrual basis, the year-end balance sheet in prior periods are still using cash toward accrual basis. Local governmentÂ  in Central Sulawesi through regulation governor Central Sulawesi no. 20 of 2014 on the accounting policies of local government Central Sulawesi Province has set up changes that serve as guidelines in carrying out the process or stages of restatement balance against the government local working unit, especially in the Agency of Community Empowerment and Village Government. Initial implementation of government accrual-based accounting system in 2015 has been included in the notes to the financial statements of the office of Community Empowerment and Village Government in Central Sulawesi. The status of audit from the financial auditor Agency is corrected or are audited despite the fact that the balance sheet restatement in 2014 has not conducted by the Agency of Community Empowerment and Village Government in Central Sulawesi.